Cycles in graphs of fixed girth with large size. (May 2017) - Solymosi, József; Wong, Ching
Abstract: Consider a family of graphs having a fixed girth and a large size. We give an optimal lower asymptotic bound on the number of even cycles of any constant length, as the order of the graphs tends to infinity.